LEGAL PROTECTION OF BARISTA WAGES AND SOCIAL SECURITY AT CIREBON COFFEE SHOP - Arie Purnomo; Deni Yusup Permana (Fakultas Hukum Universitas Swadaya Gunung Jati, 2027)
Background. The rapid growth of coffee shops in Cirebon has increased the demand for baristas, many of whom are employed as freelance daily workers under precarious employment arrangements. Despite their growing contribution to the service sector, these workers often experience inadequate legal protection regarding wages and employment social security. Aims. This study aims to analyze the implementation of legal protection for the wage and social security rights of freelance daily baristas in coffee shops in Cirebon under the framework of Law Number 6 of 2023 concerning Job Creation and related labor regulations. Methods. An empirical juridical approach was employed using qualitative methods. Primary data were collected through semi-structured interviews with officials from the Cirebon City Manpower Office, coffee shop managers, and freelance daily baristas, while secondary data were obtained from legislation, legal literature, and relevant scholarly publications. Result. The findings reveal that the implementation of labor protection remains inadequate. Many baristas work without written employment agreements, receive wages below the applicable regional minimum wage, and are excluded from the BPJS Employment social security program. Conclusion. These conditions are primarily attributed to limited employer compliance, insufficient awareness of labor rights among workers, financial constraints of small businesses, and weak governmental supervision. Consequently, a significant gap persists between statutory labor protections and their practical implementation. Implication. The study recommends strengthening labor inspections, expanding legal awareness programs, facilitating BPJS Employment registration for freelance workers, and promoting standardized written employment agreements to enhance legal certainty and social protection for freelance daily baristas in Indonesia's growing coffee shop industry.